Peningkatan Mutu Manajemen Keuangan dan Akuntansi pada UMKM Batik di Kabupaten Pati - Dwi Soegiarto; Sri Mulyani (Universitas Muria Kudus, 2022)
The purpose of this community service is to provide financial management and accounting training for Batik SMEs in Pati Regency. MSMEs have a strategic position in regional and national economic growth in general. Universities assist local governments in developing MSMEs through training, mentoring, and distribution of assistance to MSMEs. This Financial Management and Accounting Training helps MSMEs understand business performance, separate business finance from household finances, know the value of business assets, be able to make tax calculations, and can facilitate access to banking. The methods used in this community service are lectures, simulations, and discussions. This community service has been carried out well and smoothly in June 2021 in the Cooperatives and UMKM Service Hall of Pati Regency.